2016
DOI: 10.1186/s12944-016-0340-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus inhibits apolipoprotein A5 expression through its core gene

Abstract: BackgroundHepatitis B virus (HBV) infection causes lipid metabolism disorders. Apolipoprotein A5 (ApoA5) is a new apolipoprotein family member that plays an important role in the regulation of lipid metabolism. The present study was to investigate the impact of HBV on ApoA5 expression and its regulatory mechanism.MethodsReverse transcription polymerase chain reaction (RT-PCR) and western blotting were used to measure ApoA5 mRNA and protein expression in HepG2 and HepG2.2.15 cells. Enzyme-linked immunosorbent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Lower apolipoprotein B levels were found to be associated with a lower prevalence of NAFLD . Similarly, it has been suggested that HBV has an inhibitory effect on the secretion of apolipoprotein A5, a new member of the apolipoprotein family, in vivo and in vitro . It was found that knockdown of apolipoprotein A5 gene expression using small interfering RNA significantly decreased the intrahepatic triglyceride content .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Lower apolipoprotein B levels were found to be associated with a lower prevalence of NAFLD . Similarly, it has been suggested that HBV has an inhibitory effect on the secretion of apolipoprotein A5, a new member of the apolipoprotein family, in vivo and in vitro . It was found that knockdown of apolipoprotein A5 gene expression using small interfering RNA significantly decreased the intrahepatic triglyceride content .…”
Section: Discussionmentioning
confidence: 91%
“…48 Similarly, it has been suggested that HBV has an inhibitory effect on the secretion of apolipoprotein A5, a new member of the apolipoprotein family, in vivo and in vitro. 49 It was found that knockdown of apolipoprotein A5 gene expression using small interfering RNA significantly decreased the intrahepatic triglyceride content. 50 Furthermore, observational studies found that patients with current HBV infection had a decreased prevalence of hypertriglyceridemia and hypercholesterolaemia.…”
Section: Ourmentioning
confidence: 99%
“…HepG2 cells were co-transfected with all of the individual plasmid eukaryotic expression vectors containing the HBV genome and the ApoC3 gene promoter pApoC3-Luc, respectively, pCMV-tag2B was set as the control [ 11 ]. The results showed that the HBX significantly down-regulated the promoter activity of ApoC3 gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Jiang W and Wang Y confirmed the regulatory effect of HBV on ApoA1 [ 10 , 16 ]. Our previous study also demonstrated the molecular mechanism of HBV inhibition of ApoB expression and found that HBV can inhibit the expression of ApoA5 [ 9 , 11 ]. In this study, we found that the expression levels of ApoC3 mRNA and protein in HepG2.2.15 cells were lower than those in HepG2 cells, which is consistent with the microarray results of Norton PA. We also found that the expression levels of the ApoC3 promoter, mRNA and protein were inhibited by the transfection of the HBV-infected clone pHBV1.3 and HBV X gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation